THE ROLE OF ELITES IN FORMATION OF ENVIRONMENTAL CONSCIOUSNESS OF SOCIETY (HISTORICAL OVERVIEW) - Gardashuk, Tetiana; Filiyanina, Nelya (Київський національний університет імені Тараса Шевченка, 2018)
The historical role of elite (elites) in formation of the public ecological consciousness and in solving of environmental problems from the beginning of industrial revolution of 16-17 centuries in England which resulted in drastic impacts on the environment until our days are considered in the article. It was discovered the evolution of the environmental concerns from the worry of the elites about nature to the modern global mass movement. The first concern of elites over the human impacts on nature and over the loss of harmony between man and nature is related to the time of Romanticism. It was articulated in the most expressive form in the English Romanticism (Percy Bashi Shelley, William Blake, George Byron, Samuel Taylor Coleridge, William Wordsworth, John Clare) and in the German Romanticism (Friedrich Wilhelm Schelling, Novalis). The concern of the public elites (writers, scientists-naturalists, public figures, artists) of the end of the 19th and early 20th centuries over the state of the environment, natural resources depletion, species extinction and over the decline of the natural and cultural heritage in total due to rapid industrialization and urbanization created the preconditions for the modern ecologim. During that period nature is still considered as a source of harmony and stability which is able to resist to destructive power of industrial civilization, which rapidly transforms the environment. Particular features of development of the European movement for nature protection were shaped by the national, cultural, economic and political peculiarities of the countries of the Western Europe, as well as by dominating social moral and aesthetic values of particular country. The joint result of the activities of the broad spectrum of environmental organizations and groups was the adoption of legislative acts aimed at natural-cultural heritage protection of the end of the 19th and early 20th centuries in a number of European countries. This created favorable conditions for networking the European environmental movement and for internationalization of its activities and for forming the first phase of the environmental mobilization of the society, initiated by the public elites of the end of the 19th and early 20th centuries. After the Second World War the broad strata of population in the Western Europe and the North America were involved in the environmental movement. At the same time this movement was split in two principal branches, namely: the nature conservation movement and the movement which considers the quality and safety of human environment as a part of human rights in a democratic society. From 1960s there are two relatively autonomous main branches of the public movement, which, however, closely interact with each other. The formation of the second phase of environmentalism is related to the penetration of the ideas of environmental protection in all spheres of social and political life during 1960s-1970s («Silent Spring», the Club of Rome) and celebration of the Earths Day in April of the year 1970. Thus, the elitist movement for nature protection was transformed into the mass movement for human rights to live in the save environment. In spite of the environmental movement has gone the way from concerns of the elites over the growth of industrialization, urbanization and negative environmental impacts of economic growth and, consequently, overconsumption to the mass movement of thousands and millions of people, the elites still continue to play a significant role in it. Keywords: nature conservation, environmental protection, environmental crisis, environmental movement, ecologism, elites, Romanticism, «Silent Spring», the Club of Rome.

В статті розглядається історична роль еліти (еліт) у формуванні суспільної екологічної свідомості та у розв’язанні екологічних проблем загалом від початку промислової революції 16–17 ст. в Англії, яка спричинила суттєвий сплив на природне довкілля, і до наших днів. Перші прояви стурбованості еліт людським впливом на природу та втратою гармонії між людиною та природою пов’язані з епохою Романтизму і найбільш виразно були артикульовані в англійському (Персі Біші Шеллі, Блейк, Дж.Байрон, Колридж, Вільям Вордсворт, Дж. Клер) на німецькому романтизмі (Фрідріх Вільгельм Шеллінг, Новаліс). Стурбованість суспільних еліт (письменників, вчених-натуралістів, громадських діячів, митців) кінця 19–початку 20 ст. станом довкілля, виснаженням природних ресурсів, втратою багатьох видів рослин і тварин, занепадом природно-культурної спадщини загалом, що їх зумовила стрімка індустріалізація й урбанізація західного суспільства, формує передумови сучасного екологізму. В цей час природу продовжують розглядати як джерело гармонії та стабільності, що здатне протистояти руйнівній силі індустріальної цивілізації, яка стрімко змінювала навколишній світ. Особливості становлення європейського руху за збереження природи зумовлювалися національними, культурними, економічними й політичними особливостями країн Західної Європи, а також домінантними суспільними моральними й естетичними цінностями тієї чи тієї європейської країни. Спільним наслідком діяльності широкого спектра природоохоронних організацій і товариств стало ухвалення відповідних законодавчих актів кінця 19–початку 20 ст. у низці країн Європи. Це створило сприятливі умови для розвитку європейської мережі природоохоронного руху й інтернаціоналізації його діяльності та формування першої хвилі екологічної мобілізації, що її ініціювали суспільні еліти кінця 19–початку 20 ст. Після Другої світової війни екологістський рух охопив широкі верстви населення у промислово розвинених країнах Західної Європи й Північної Америки. Відбулася своєрідна біфуркація руху за збереження природи на власне природоохоронний рух і рух за охорону довкілля та якості життя людини як складової боротьби за права людини. Від1960-х років вони становлять дві потужні гілки суспільно-політичного руху, але, незважаючи на відносну автономію, тісно взаємодіють між собою. Становлення другої хвилі екологізму пов’язують з початком екологізації всіх сфер суспільно-політичного життя упродовж 1960-х – 1970-х років та з запровадженням відзначення Дня Землі у квітні 1970 р. Таким чином відбулася трансформація елітарного руху на захист природи і довкілля на масовий рух за екологічні права людини та збереження природи. Незважаючи на те, що екологістський рух пройшов шлях від стурбованості еліт, викликаної наступом індустріалізації, розширеного сільськогосподарського виробництва, урбанізації на природу та негативними наслідками економічного зростання загалом і, відповідно, зростанням споживання, до руху масового, в якому беруть безпосередню участь тисячі й мільйони людей, еліти продовжують відігравати у ньому вагому роль. Ключові слова: охорона природи, екологічна кризи, екологічний рух, екологізм, еліти, Романтизм, «Мовчазна весна», Римський клуб.
РОЛЬ ЕЛІТ У ФОРМУВАННІ ЕКОЛОГІЧНОЇ СВІДОМОСТІ СУСПІЛЬСТВА (ІСТОРИЧНИЙ ЕКСКУРС)